2011
DOI: 10.1007/s11096-011-9568-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug dosing and monitoring in obese patients undergoing allogenic stem cell transplantation

Abstract: Pharmacotherapy in morbidly obese patients undergoing allogenic stem cell transplantation is possible, if pharmacokinetic properties of the drugs are considered and close monitoring of plasma concentrations is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Guidelines were recently published recommending use of actual weight and BSA for patients with abnormal BSA if the intent of therapy is cure . Clearance of drugs by glomerular filtration and metabolism by various cytochrome systems has been shown to differ in obese and non‐obese patients . However, little information is available on differences in pharmacokinetics between obese and non‐obese individuals for drugs used in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines were recently published recommending use of actual weight and BSA for patients with abnormal BSA if the intent of therapy is cure . Clearance of drugs by glomerular filtration and metabolism by various cytochrome systems has been shown to differ in obese and non‐obese patients . However, little information is available on differences in pharmacokinetics between obese and non‐obese individuals for drugs used in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Langebrake et al [154], in providing recommendations for morbidly obese patients undergoing allogeneic haematopoietic stem cell transplantation, suggested that IBW be used due to the hydrophilic nature and high renal clearance of cotrimoxazole; however, this recommendation was not based on any patient data. Halilovic et al [111 & ] found morbidly obese patients with cellulitis AE cutaneous abscess given inappropriately low doses of cotrimoxazole or clindamycin on discharge had significantly higher rates of treatment failure; the authors suggested dosing of these antibiotics be based on patient's body mass (i.e.…”
Section: Cotrimoxazole Clindamycinmentioning
confidence: 99%
“…To meet the health needs and safe use of drugs by a patient with morbid obesity, specific material was also developed on the dose adjustment of the drugs most employed in HSCT according to actual weight, adjusted ideal weight or body surface. [29][30][31] Considering the frequent contacts of the other health professionals with the themes approached in the educational materials prior to their elaboration, we believe that they had a relevant impact in avoiding DRPs and qualifying the care offered. A systematic review published recently concluded that such materials can slightly improve the health practices.…”
Section: Discussionmentioning
confidence: 99%